2021
DOI: 10.1001/jamaoto.2021.0760
|View full text |Cite
|
Sign up to set email alerts
|

Trend Analysis of Cutaneous Squamous Cell Carcinoma of the External Lip From 1975 to 2016

Abstract: utaneous squamous cell carcinoma (cSCC) is the second most common nonmelanoma skin cancer, with an incidence between 5 and 96 per 100 000 individuals. 1,2 Most patients with this malignant neoplasm are diagnosed early and treated surgically with disease-free survival. However, between 3.7% and 5.8% of cases metastasize, leading to 4000 to 9000 deaths annually in the United States. 3 Cutaneous SCC of the head and neck (cHNSCC) is a primary site of special concern. Commonly affected sites in this region are the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 45 publications
1
2
0
1
Order By: Relevance
“…People with fair skin have less melanin and less protection against UVR ( 20 22 ). Consistent with the results of previous studies, cSCC on the lips was most common in white people ( 22 ) and less common in black people, Indians, and Asians ( 23 , 24 ). It is more common in men than in women, with a male-to-female ratio of up to 4:1 ( 22 , 25 ).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…People with fair skin have less melanin and less protection against UVR ( 20 22 ). Consistent with the results of previous studies, cSCC on the lips was most common in white people ( 22 ) and less common in black people, Indians, and Asians ( 23 , 24 ). It is more common in men than in women, with a male-to-female ratio of up to 4:1 ( 22 , 25 ).…”
Section: Discussionsupporting
confidence: 91%
“…cSCC on the lips is prevalent in people over 40 years of age, with the highest incidence in 60–79 years, and incidence-based morbidity increases over 80 years old. The elderly were relatively vulnerable, and the 5-year disease-specific survival rate of patients aged over 75 years old, especially those over aged 85 years old, is relatively poor ( 23 ). A study has found that old age is not a risk factor for poorer survival in metastatic cSCC on the lips, which might be limited to metastatic cSCC on the lips disease ( 48 ).…”
Section: Discussionmentioning
confidence: 99%
“… Proportion of males with cSCC of the total head and neck region [ 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 ...…”
Section: Figureunclassified
“… Proportion of males with cSCC of lips [ 17 , 21 , 23 , 35 , 38 , 45 , 48 , 49 , 51 , 54 , 62 , 70 ]. …”
Section: Figurementioning
confidence: 99%